Identities in Early Medieval Dalmatia (7th - 11th c.) - Budak, Neven (Array, 2008)
The paper investigates the development of identities in early medieval Dalmatia/Croatia by analysing sources of different origin. Apart from the more general Slavic and Roman identities, there are also more speciphic ones. The Croatian identity emerges in the first half of the ninth c., but is at that time recognised only within Dalmatia. In the tenth c. sources from other regions start to recognise this identity.